“I Should be Able to Play Already!” Promoting Self-Direction in Adult Piano Students through Transformational Learning Strategies - Leah Coutts (Adult Education Research Conference, 2015)
Can transformational learning strategies help a piano teacher foster self-direction in her adult piano students? My journey suggests it can, but not without some discomfort and bumps along the way.
Keywords: transformational learning; piano pedagogy; adult piano students; self-direction; critical reflection